Survey of the natural enemies of the crazy ant, Paratrechina fulva (Hymenoptera: Formicidae), in the municipality of El Colegio (Cundinamarca) and in the Cauca River valley - VARGAS-O., GERMÁN ANDRÉS; DÍAZ-P., PAULA ANDREA; LASTRA-B., LUZ ADRIANA; MESA-C., NORA CRISTINA; ZENNER DE POLANÍA, INGEBORG; GÓMEZ, LUIS ANTONIO (Revista Colombiana de Entomología, 2004)
The crazy ant (CA) has become an environmental, social and economic problem and there is a need to explore for natural enemies that might regulate its populations. With that objective, a survey was conducted by means of visual observation and captures of CA and other ants in two zones: El Colegio (Cundinamarca) representing a zone once highly infested by this pest and the Cauca RiverValley where there are areas currently affected by the CA. CA was not caught in El Colegio but a large number of ant species belonging to other genera and subfamilies were collected. Under these conditions, it was not possible to detect natural enemies, but equilibrium was reestablished together with the disappearance of CA, with no clear explanation up to now. In the Cauca Valley, no pathogens and parasitoids were found other than the mite Macrodinychus sellnicki, which was found parasitizing O to 82% of CA pupae in the Risaralda and INCAUCA, S. A. sugar milis, respectively. In field observations the army ant, Labidus pos. coecus, which feeds on others ants was detected in CA nests. In the least disturbed sarnpled, La Trozada, CA was detected in the presence of other native ants, in a situation where competition for resources constitutes an important element in the regulation of pest populations. These situations suggest that high levels of CA infestation are not permanent and their duration is influenced by characteristics of the areas they invade. The importance of natural enemies is that they weaken CA populations, allowing competitors, particularly other ants, to reduce them in infested areas.